Bimodal fluorescence/129Xe NMR probe for molecular imaging and biological inhibition of EGFR in Non-Small Cell Lung Cancer. Issue 24 (15th December 2017) - Milanole, Gaëlle; Gao, Bo; Paoletti, Audrey; Pieters, Grégory; Dugave, Christophe; Deutsch, Eric; Rivera, Sofia; Law, Frédéric; Perfettini, Jean-Luc; Mari, Emilie; Léonce, Estelle; Boutin, Céline; et al.
Graphical abstract: Abstract: Although Non-Small Cell Lung Cancer (NSCLC) is one of the main causes of cancer death, very little improvement has been made in the last decades regarding diagnosis and outcomes. In this study, a bimodal fluorescence/ 129 Xe NMR probe containing a xenon host, a fluorescent moiety and a therapeutic antibody has been designed to target the Epidermal Growth Factor Receptors (EGFR) overexpressed in cancer cells. This biosensor shows high selectivity for the EGFR, and a biological activity similar to that of the antibody. It is detected with high specificity and high sensitivity (sub-nanomolar range) through hyperpolarized 129 Xe NMR. This promising system should find important applications for theranostic use.